Efficacy of Dietary Supplementation with Capsicum Annum L on Performance, Hematology, Blood Biochemistry and Hepatic Antioxidant Status of Growing Rabbits - Hamada Elwan; Mostafa Abdelhakeam; Sally El-Shafei; Atef Abd El-Rahman; Zienhom Ismail; Abdalrahman Zanouny; Emad Shaker; Salim S. Al-Rejaie; Mohamed Mohany; Shaaban Elnesr (Animals, 2020)
Animals fed with a high amount of a wide range of antioxidants in their diet are significantly protected against oxidative stress. Powerful antioxidant substances such as vitamin E, vitamin C, and carotenoids are present naturally in red-hot pepper (RHP). This study hypothesized that using RHP may provide protection against oxidative stress and enhance animal physiological responses. Thus, this study aimed to investigate the effect of feeding New Zealand white rabbits with RHP-supplemented diets on their physiological and biochemical responses. New Zealand White rabbits (age = 6 weeks, n = 48) were split equally into three groups (n = 16 in each group). One group was fed a basal diet only (control group), with the other two groups fed a basal diet along with 1 and 2% RHP. Mass spectrometric analysis for the RHP methanolic extract showed some phenolic compounds, such as p-coumaric, sinapinic acids, vanillic, and luteolin, as well as catechin and its isomers. Hepatic antioxidant enzymes (SOD, GSH, GSH-Px, and CAT) were significantly elevated (p < 0.05) by feeding rabbits diets supplemented with 1 or 2% RHP. The addition of RHP significantly enhanced immune-responses; phagocytic activity, chemotaxis, TIg, IgG, IgM, and IgA increased when growing rabbits were fed RHP compared with the control group. In conclusion, dietary supplementation of 1 or 2% RHP may play a role as an enhancer of growth and immune response in growing rabbits.